Public value deepening, enriching, and broadening the theory and practice - Lindgreen, Adam; Koenig-Lewis, Nicole; Kitchener, Martin; Brewer, John D.; Moore, Mark H.; Meynhardt, Timo (Routledge, 2019)
"Over the last 10 years, the concept of value has emerged in both business and public life as part of an important process of measuring, benchmarking and assuring the resources we invest and the outcomes we generate from our activities. In the context of public life, value is an important measure on the contribution to business and social good of activities for which strict financial measures are either inappropriate or fundamentally unsound. This ground-breaking research anthology explores public value in the context across a wide range of contextually and culturally diverse examples including public management (leadership, public procurement, voluntary activity, knowledge management, co-creation); cultural heritage; education and research. Collectively the anthology offers new ways of looking at public and social assets against a backdrop of increasing financial pressure; new insights into changing social attitudes and perceptions of value; and new models for increasingly complicated collaborative forms of service delivery, involving public, private and not-for-profit players."--Provided by publisher